Towards sustainable palm oil production: the positive and negative impacts on ecosystem services and human wellbeing - Ayompe, L.M.; Schaafsma, M.; Egoh, B.N. (Elsevier, 2021)
Palm oil is an important commodity contributing to livelihoods of many communities, GDP of governments and the achievement of several sustainable development goals (SDG) including no poverty, zero hunger, and decent work and economic growth. However, its cultivation and continuous expansion due to high and increasing demand has led to many negative effects and subsequent calls to make production sustainable. To this end, information is needed to understand the negative and positive impacts on both the environment and human wellbeing to respond appropriately. Sustainability in palm oil trade entails having a global supply chain based on environmentally friendly and socially acceptable production and sourcing. Much has been done in understanding and responding to impacts on the environment but not so much on social impacts partly due to a lack of information. The direct (socio-economic) and indirect (through ecosystem services) impacts of palm oil trade were reviewed using peer-reviewed literature and the Environmental Justice Atlas (EJA). Our results show that most of the 57 case studies were conducted in Indonesia and Malaysia where 85% of global production of palm oil occurs. The results show both negative (109) and positive (99) direct impacts on humans. Indirect impacts through ecosystems services were predominantly negative (116) as were the direct negative impacts. The most frequently studied direct negative impacts were conflicts (25%), housing conditions (18%) and land grabbing (16%) while the most frequently studied direct positive impacts were income generation (33%) and employment (19%). Ongoing initiatives to make the palm oil sector sustainable such as the RSPO are focused on the environment but need to pay more attention to (related) social impacts. To make palm oil production sustainable and to meet SDGs such as ensuring healthy lives and promoting wellbeing as well as responsible consumption and production, negative social impacts of palm oil trade need to be addressed.